2014
DOI: 10.1140/epjc/s10052-014-2802-x
|View full text |Cite
|
Sign up to set email alerts
|

Is Eddington–Born–Infeld theory really free of cosmological singularities?

Abstract: The Eddington-inspired-Born-Infeld (EiBI) theory has recently been resurrected. Such a theory is characterized by being equivalent to Einstein theory in vacuum but differing from it in the presence of matter. One of the virtues of the theory is that it avoids the Big Bang singularity for a radiation-filled universe. In this paper, we analyze singularity avoidance in this kind of model. More precisely, we analyze the behavior of a homogeneous and isotropic universe filled with phantom energy in addition to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 24 publications
(42 reference statements)
1
45
0
Order By: Relevance
“…More relevant studies can be found in Refs. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. It was shown in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…More relevant studies can be found in Refs. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. It was shown in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[12] that it has curvature singularities at the surface of polytropic stars and unacceptable Newtonian limit. The Big Rip singularity was found to be unavoidable in the EiBI phantom model [13]. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recall that the EiBI theory recovers GR when |κ R| is very small as shown in [24]. On the other hand, the conservation equation, as mentioned previously, takes the standard form…”
Section: The Eibi Model and Dark Energy Related Singularitiesmentioning
confidence: 84%
“…We showed recently that despite the big bang avoidance in the EiBI setup, the big rip [49][50][51][52][53][54][55][56] is unavoidable in the EiBI phantom model [1]. In this paper, we will assume an EiBI model and we will carry a thorough analysis of the possible avoidance of the other dark energy related singularities, known as: (i) sudden, type II, big brake or big démarrage singularity [57][58][59][60], (ii) type III or big breeze singularity [59][60][61][62][63] and (iii) type IV singularity [59,60,64,65].…”
Section: Introductionmentioning
confidence: 99%